2012
DOI: 10.1007/s00128-012-0950-y
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and Mercury in Native Aquatic Bryophytes: Differences Among Species

Abstract: This study investigated the capacities of five species of aquatic bryophytes to accumulate As and Hg from their natural habitats in rivers in Galicia (NW Spain). The distributions of the concentrations of both elements in all species were skewed to the right, with a higher incidence of extreme values in the As data, which may indicate a greater degree of contamination by this metalloid. There were no significant differences in the accumulation of either of the elements between the different species studied, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The sampling location was in an undisturbed area, where atmospheric deposition could be suggested as a source of contamination. A similar median Hg concentration (101 ng g −1 ) was reported for F. antipyretica from rivers throughout Galicia, Spain [ 24 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The sampling location was in an undisturbed area, where atmospheric deposition could be suggested as a source of contamination. A similar median Hg concentration (101 ng g −1 ) was reported for F. antipyretica from rivers throughout Galicia, Spain [ 24 ].…”
Section: Discussionsupporting
confidence: 75%
“…The hypothesis that different moss species can be adopted as biomonitors and can reveal pollution patterns has been already been confirmed [ 16 ]. The lack of significant differences in the accumulation of As and Hg between five aquatic bryophytes ( F. antipyretica , P. riparioides , S. undulata , B. rivulare, and F. polyphyllus ) justified their combined use as biomonitors [ 24 ]. Three moss and two submerged vascular plant species that were applied as biomonitors in the current study confirmed the above-mentioned findings and revealed the possibility of combining aquatic mosses and vascular plants to meet the needs of rapid assessment.…”
Section: Discussionmentioning
confidence: 99%